Activation of Multiple Transcriptional Regulators by Growth Restriction in Pseudomonas aeruginosa - Yeom, Doo Hwan (Korean Society for Molecular and Cellular Biology, 2014)
Growth restriction by antibiotics is a common feature that pathogenic bacteria must overcome for survival. The struggle of bacteria to escape from growth restriction eventually results in development of antibiotic-resistance through the expression of a set of genes. Here we found that some physiologically important transcriptional regulators of Pseudomonas aeruginosa including QscR, a quorum sensing (QS) receptor, SoxR, a superoxide sensor-regulator, and AntR, a regulator of anthranilate-related secondary metabolism, are activated by various growth-restricted conditions. We generated the growth-restricted conditions by various methods, such as overexpression of PA2537 and treatment with antibiotics or disinfectants. The overexpression of PA2537, encoding an acyltransferase homologue, tightly restricted the growth of P. aeruginosa and significantly activated QscR during the growth restriction. Similarly, treatments with gentamycin, tetracycline, and ethanol also activated QscR near their minimal inhibitory concentrations (MICs). Some non-QS regulators, such as AntR and SoxR, were also activated near the MICs in the same conditions. However, LasR and PqsR, other QS receptors of P. aeruginosa, were not activated, suggesting that only a specific set of transcriptional regulators is activated by growth restriction. Since paraquat, a super-oxide generator, significantly activated QscR and AntR, we suggest that the oxidative stress generated by growth restriction may be partly involved in this phenomenon.